Pendidikan Akhlak Anak Dalam Perspektif Abdulah Nasih Ulwan dan Relevansinya dengan kondisi saat ini - Erfa Ernawati (Adabiyah : Jurnal Pendidikan Islam, 2017)
The purpose of national education is to develop the potential of learners to become human beings who believe and cautious to God Almighty, have noble character, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible. In fact, although the number of educated people is increasing, there is still a lot of criminality, immorality, violation of law and other issues as if eliminating the identity of a nation that berpencasila. This is where the importance of morals, the role of morals in life is often beyond the role of science, for science without morality encourages people to the kebiadapan ". So it becomes a necessity for all educators, the public as well as the state to focus on matters of morality, by realizing that children's time is the right time to instill morals. An effective method is needed to instill morals to the children, and in this case we are referring to Abdullah Nasih Ulwan who has made the formula for the education of morals for children in accordance with the rules of the current education. Departing from the background mentioned above, In order for research to have direction, base and meaning, it is necessary writer to formulate the purpose of this research, namely: first, to know urgency of moral education in children according to Abdullah Nasih Ulwan, second to know the method and application of moral education on according to Abdullah Nasih Ulwan, the third to know its relevance to the current conditions.